1992
DOI: 10.1002/aic.690380311
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of mixing and polymerization in a semibatch stirred‐tank reactor

Abstract: Effects of mixing on number-and weight-average degree of polymerization in free radical homopolymerization in solution in a semibatch stirred tank-reactor have been modeled by use of the "partially segregated feed" model of Villermaux (1989) and the lumped kinetic treatment of addition polymerization. Mixing conditions are described in terms of the dimensionless time constants OM and 0, for convective and diffusive mixing, respectively. Results show that DP,, is relatively insensitive, while DP, is highly sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Viscosities of polystyrene solutions were characterized in many previously published works. [40][41][42] In order to describe the viscosity of the reacting system, the Harkness [43] correlation (Equation (19)) was used for monomer conversions smaller than 0.4, while the Mendelson [41,42] correlation (Equation (20)) was used for monomer conversions higher than 0.4. Particularly, these correlations have been used successfully to perform simulations in other works.…”
Section: Description Of Thermo-kinetic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Viscosities of polystyrene solutions were characterized in many previously published works. [40][41][42] In order to describe the viscosity of the reacting system, the Harkness [43] correlation (Equation (19)) was used for monomer conversions smaller than 0.4, while the Mendelson [41,42] correlation (Equation (20)) was used for monomer conversions higher than 0.4. Particularly, these correlations have been used successfully to perform simulations in other works.…”
Section: Description Of Thermo-kinetic Parametersmentioning
confidence: 99%
“…[15,16] Several other studies have investigated the influence of imperfect mixing on the dynamic behavior of polymerization reactors and polymer properties by assuming compartmental modeling. [17][18][19][20][21][22][23] These works showed that the bifurcation behavior of the polymerization systems can be very sensitive to compartmentalization, indicating that the dynamic behavior of the whole process can be affected by mixing effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, they can also represent some degree of micromixing if diffusion is allowed between different zones (Villermaux, 1989a). Compartmental models have been used to study imperfect mixing in continuous LDPE autoclave (Marini and Georgakis, 1984a;Chan et al, 1993) and a semibatch reactor (Tosun, 1992). They have also been used to study the influence of mixing on reactor stability and interaction of mixing and gelation (Kalbfleisch and Teymour, 1995).…”
Section: Fluid-jbw Modelsmentioning
confidence: 99%
“…1984a1, copolymer composition distribution (CCD) (Atiqullah and Nauman, 1990;Mecklenburgh, 1970;O'Driscoll and Knorr, 1969), and the molecular-weight distribution (MWD) (Tadmor and Biesenberger, 1966;Marini and Georgakis, 1984b;Tosun, 1992). The mean values of CCD and MWD are less affected than the breadth of the distributions, which often increases with poorer mixing.…”
Section: Introductionmentioning
confidence: 98%
“…After radial derivative discretization, the nonlinear system of ordinary differential equations obtained was numerically integrated through an implicit integration method (the Adams–Moulton method). The most important characteristic of this implicit integration method is its capability to overcome stiffness problems, frequently reported in modeling and simulation studies on polymerization systems 27–29…”
Section: Mathematical Model and Numerical Simulationmentioning
confidence: 99%